Appreciating Factors Beyond the Physical in Talent Identification and Development: Insights From the FC Barcelona Sporting Model - Doncaster, Greg; Medina, Daniel; Drobnic, Franchek; Gómez-Díaz, Antonio José; Unnithan, Viswanath (Frontiers in Sports and Active Living, 2020)
The relative age effect is a selection bias toward those individuals born earlier within the selection-year. This study sought to evaluate the relative age effect (RAE) within an elite multi-sport context; FC Barcelona. The birth-dates of all players (n = 6542) affiliated to each sport (male Basketball [n = 1013], male [n = 3012] and female [n = 449] Soccer, male Futsal [n = 761], male Handball [n = 999] and male Indoor Roller Hockey [n = 308]) across all age groups from U10 to Senior were recorded. These were then categorised into quartiles from the start of the selection year (Q1=Jan-Mar; Q2=Apr-Jun; Q3=Jul-Sep; Q4=Oct-Dec) and analysed for; a) each sport, b) each age group, irrespective of the sport and c) each age group within each sport, using Chi-squared statistics and odds ratio’s (OR) with 95% confidence intervals. Birthdates across the entire club revealed a RAE (Q1= 46.1%, Q2= 27.1%, Q3=17.1% & Q4 = 9.7%, X2 = 29.8, P < 0.01), with OR in Q1, Q2 and Q3 representing a 4.76 (95% CI’s:1.96-11.57), 2.80 (1.12-7.03) and 1.77 (0.67-4.63) increased likelihood for selection, when compared to Q4, respectively. Despite a talent identification model that primarily uses psychological and perceptual-cognitive markers, the RAE was still present within youth age groups (<18 yrs old). The current findings provide support that the RAE is more prevalent within high-profile sports and reduces with increasing age, however, given the talent identification processes within the current context, additional factors beyond the physical dominance, such as enhanced psychological and perceptual-cognitive attributes, in those born earlier in the selection year may further exacerbate the RAE.